Perioperative management of positioning in gynecological cancersurgery: a national NOGGO-AGO intergroup survey. Issue 10 (16th October 2020) - Bommert, Mareike; Wagner, Jenny Katharina; Sehouli, Jalid; Burges, Alexander; Schmalfeld, Barbara; Veldink, Hendrik; Schrettenbrunner, Irmela; Fleisch, Markus; Richter, Rolf; Harter, Philipp; Pietzner, Klaus
Abstract : Introduction: The daily clinical routine in the operating room includes patient positioning. The number of perioperative positioning-related complications is growing, along with the legal proceedings concerning this topic, and only a few guidelines exist to provide specific recommendations. The aim of this survey was to assess perioperative positioning and associated adverse events during gynecological cancer surgery in Germany. Methods: A total of 633 gynecological departments of primary, secondary, and maximum healthcare hospitals in Germany were invited to participate in this multiple-choice online questionnaire. The survey was conducted anonymously for a period of six months. The survey was divided into five different sections: descriptive information about the respondent department, pre- and postoperative management, management of positioning in the operating room based on two fictional case examples, and quality management. Results: The response rate of our survey was 29.1 % (184/633). Nearly half of the departments (46.7 %) reported to have had one to five patients with positioning-related complications during the prior 12 months, and 29.1 % had experienced a legal dispute due to positioning-related complications. Departments with more than 50 gynecologic-oncological surgeries per year more often reported positioning-related complications (p=0.003). Standard operating procedures exist in almost every department for laparoscopic (97 %) and open surgery (95.1 %), respectively. Discussion: The high number of positioning-related complications throughout all departments of different healthcare levels underlines the relevance of this issue and supports the need for a prospective European registry for further analysis. Training and education for all staff members should be routinely implemented to reduce and prevent positioning-related complications.